Utility of N-Bromosuccinimide for the Titrimetric and Spectrophotometric Determination of Famotidine in Pharmaceutical Formulations - O. Zenita; K. Basavaiah (International Journal of Analytical Chemistry)
Two titrimetric and two spectrophotometric methods are described for the assay of famotidine (FMT) in tablets using N-bromosuccinimide (NBS). The first titrimetric method is direct in which FMT is titrated directly with NBS in HCl medium using methyl orange as indicator (method A). The remaining three methods are indirect in which the unreacted NBS is determined after the complete reaction between FMT and NBS by iodometric back titration (method B) or by reacting with a fixed amount of either indigo carmine (method C) or neutral red (method D). The method A and method B are applicable over the range of 2–9 mg and 1–7 mg, respectively. In spectrophotometric methods, Beer's law is obeyed over the concentration ranges of 0.75–6.0 μg mL-1 (method C) and 0.3–3.0 μg mL-1 (method D). The applicability of the developed methods was demonstrated by the determination of FMT in pure drug as well as in tablets.